P.043 Cannabis treatment in children with epilepsy: practices and attitudes of neurologists in Canada. (June 2019) - DeGasperis, SM; Webster, R; Pohl, D
Abstract : Background: Cannabis has been shown to be an effective therapy for epilepsy in children with Dravet and Lennox-Gastaut syndrome. Despite the fact that many pediatric epilepsy patients across Canada are currently being treated with cannabis, little is known about pediatric neurologists' attitudes towards it. Methods: A 26-item online survey was distributed to 148 pediatric neurologists across Canada. Results: 56/148 neurologists responded and reported that over 600 children with epilepsy are currently taking cannabinoids. 34% of neurologists authorized cannabis to children, 38% referred children for authorization, and 29% did not authorize or refer their patients. Of those neurologists who referred, 76% referred to a community-based non-neurologist. The majority of physicians authorized cannabis to patients with Dravet syndrome (68%) and Lennox-Gastaut syndrome (64%). Cannabis was never authorized as a first-line treatment. 54% of neurologists stated that their patients were taking CBD alone, despite this option not being available in Canada. All physicians reported having at least one hesitation regarding cannabis, the most common ones being poor evidence (66%), poor quality control (52%), and cost (50%). Conclusions: The majority of Canadian pediatric neurologists use cannabis as a treatment for epilepsy in children. However, there appear to be knowledge gaps and hesitations.